Rejection of the synonymization of Pegosomum saginatum (Ratz, 1898) Ratz, 1903 with Pegosomum asperum (Wright, 1879) Ratz, 1903 - Heneberg, Petr; Sitko, Jiljí (Parasitology international, 2017)
The Pegosomum Ratz, 1903 are digenean parasites of piscivorous birds. They exhibit few morphological autapomorphies and some of their identification features (number of collar spines) can be altered before or during fixation. Several re-classifications within the genus were suggested, but they have never been supported by molecular analyses. We addressed the synonymization of species within Pegosomum asperum/saginatum complex suggested by Dubinin, Dubinina and Saidov. We analyzed one nuclear (ITS2) and two mitochondrial (CO1, ND1) loci of two central European species of Pegosomum, namely Pegosomum asperum (Wright, 1879) Ratz, 1903 and Pegosomum saginatum (Ratz, 1898) Ratz, 1903. Our combined molecular and comparative morphological analyses confirmed the validity of the two Pegosomum spp. Both species had highly similar morphology and occurred sympatrically in the gall bladder and bile duct of Ardea alba (Linnaeus, 1758). P. saginatum occurred more frequently in hosts infected concurrently with P. asperum. We also provided host-, age- and sex-specific prevalence and intensity of infections, and comparative measurements of the two Pegosomum spp. based on an extensive dataset collected from 1962 to 2016. These species can be morphologically distinguished based on the extent of vitellarium, which reached anteriorly to the pharynx in P. asperum but extended anteriorly to the midline of the esophagus in P. saginatum. The species also differed in the cirrus diameter (P. asperum≥447, P. saginatum≤447).
Keywords: Biliary Tract; Animals; Bile Ducts; Trematoda; Birds; Female; infekce červy třídy Trematoda; Concurrent infection; Trematode Infections; DNA, Mitochondrial; ženské pohlaví; Gall bladder; Coinfection; Sympatric evolution; Biliary tract; nemoci ptáků; mezerníky ribozomální DNA; ptáci; koinfekce; Phylogeny; Bird Diseases; Heron; Bile duct; Male; mitochondriální DNA; DNA, Ribosomal Spacer; zvířata; mužské pohlaví; fylogeneze; žlučové cesty; žlučové ústrojí